1997
DOI: 10.1089/ees.1997.14.113
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Ground Granulated Blastfurnace Slag as a Toxic Waste Solidification/Stabilization Reagent

Abstract: This study summarizes an investigation into the performance of different ground granulated blastfurnace slag (GGBS)-based binders in toxic waste solidification/stabilization (S/S). The properties of two real industrial heavy metal wastes solidified/stabilized (S/S) with GGBS-based binders, including conventional ordinary Portland cement (OPC) + GGBS mixes and alkali-activated slag (AAS), were compared with those of wastes treated with conventional S/S systems involving OPC and 50% OPC + 50% pulverized fuel ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Ahmed & Buenfeld [ 122 ] also reported that nickel and molybdenum were reported to be relatively insensitive to Eh conditions, but with the possibility of mobilisation due to the higher pH environment within alkaliactivated BFS binders. In the same discussion, elements (such as As, Sb and Sn) which form soluble complexes with reduced sulfur species were also predicted to be unsuited to treatment in alkali-activated BFS systems [ 122 ]; the literature data summarised in Fig. 12.7 display that this prediction has to date proven to be accurate.…”
Section: Alkali-activated Bfs Cementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmed & Buenfeld [ 122 ] also reported that nickel and molybdenum were reported to be relatively insensitive to Eh conditions, but with the possibility of mobilisation due to the higher pH environment within alkaliactivated BFS binders. In the same discussion, elements (such as As, Sb and Sn) which form soluble complexes with reduced sulfur species were also predicted to be unsuited to treatment in alkali-activated BFS systems [ 122 ]; the literature data summarised in Fig. 12.7 display that this prediction has to date proven to be accurate.…”
Section: Alkali-activated Bfs Cementsmentioning
confidence: 99%
“…The sulfi de present in slag has been noted to be particularly helpful in generating a reducing redox environment within the pore solution, which converts Cr(VI) to Cr(III) to reduce its mobility [ 120 , 122 ]. This change in redox chemistry does oxidise Fe(III) to Fe(II) and render it more mobile [ 122 ], but the toxicity of Fe(II) is much lower than that of Cr(VI), so this is less likely to be problematic. Ahmed & Buenfeld [ 122 ] also reported that nickel and molybdenum were reported to be relatively insensitive to Eh conditions, but with the possibility of mobilisation due to the higher pH environment within alkaliactivated BFS binders.…”
Section: Alkali-activated Bfs Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role and importance of CaO content in fly ash has been discussed by many researchers [29,30,31], and it can be concluded that simply comparing the CaO content in fly ashes cannot give a clear prediction on the influence on strength of AAFAC. Some of the literature reports low CaO ashes show higher strength development [29,30], while other report the opposite [31].…”
Section: Factors Affecting the Properties Of Aafacmentioning
confidence: 99%
“…The role and importance of CaO content in fly ash has been discussed by many researchers [29,30,31], and it can be concluded that simply comparing the CaO content in fly ashes cannot give a clear prediction on the influence on strength of AAFAC. Some of the literature reports low CaO ashes show higher strength development [29,30], while other report the opposite [31]. The results obtained by analysis of the hydrated AAFAP indicate that a high content of vitreous phase and low calcium content are important factors determining the reactivity and the performance of fly ashes in alkali activated systems [30].…”
Section: Factors Affecting the Properties Of Aafacmentioning
confidence: 99%